Images of protest in contested social media: Production, propagation, and narratives - Rossi, Luca; Neumayer, Christina; Vulpius, Julie (AoIR Selected Papers of Internet Research, 2016)
Despite the widely recognized centrality of images in contemporary activists communication empirical studies based on visual social media data are rare. This article addresses this challenge by analysing images (photos and videos) produced and propagated in the Blockupy Frankfurt protests against the opening of the European Central Bank (ECB) headquarters in Frankfurt am Main, Germany, on March 18, 2015. The article enhances our understanding of visual communication in protest and social media by exploring how different conflictual visual narratives produced by different actors emerge during the Bockupy Frankfurt protests on Twitter using event-specific hashtags (#Blockupy, #Destroika, #NoTroika). This research combines a content analysis of the most retweeted visual content (1%, N=119) with a narrative analysis of photos and videos. The article concludes by arguing that on Twitter, images of riots, peaceful protests, artistic action, as well as activists, police and news media struggle for public visibility. Different actors create parallel narratives representing a positive image of themselves by antagonising the other through visual narratives of physical and latent violence (particularly in images posted by the police Frankfurt am Main but also by activists) as well as (in the case of the activists) by a non-violent and colourful positive self-representation. Despite these non-violent narratives produced by activists we can observe a dominance of physical and latent violence in reporting about protest events through visual content on Twitter.